Parental Feeding Style dan Picky Eating Behaviour terhadap Kejadian Stunting pada Anak Usia Prasekolah - Indra Dewi; Aida Rahayu; Susi Sastika Sumi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the relationship between parental feeding style and picky eating behavior on the incidence of stunting in preschool children. The research method uses a cross sectional design. The results of the research show that there is a relationship between parental feeding style and the incidence of stunting (p = 0.028) and there is a relationship between picky eating behavior and the incidence of stunting (p = 0.017) in Panaikang Village, Pattallassang District, Gowa Regency. In conclusion, there is a relationship between parental feeding style and picky eating behavior on the incidence of stunting in preschool-aged children in Panaikang Village, Pattallassang District, Gowa Regency. Keywords: Preschool Children, Parental Feeding Style, Picky Eating Behaviour, Stunting